2006
DOI: 10.1002/chir.20327
|View full text |Cite
|
Sign up to set email alerts
|

Application of preferential crystallization to resolve racemic compounds in a hybrid process

Abstract: The application of preferential crystallization is at present limited to conglomerate forming systems, which cover only a minor part of chiral substances. In this paper, a hybrid process is proposed that extends the applicability of the preferential crystallization principle to the more common racemic compound forming systems. It comprises a preliminary (e.g., chromatographic) enantiomeric enrichment step and preferential crystallization to finally produce the desired pure enantiomer(s). The applicability of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 20 publications
2
79
0
6
Order By: Relevance
“…The SMB technology was a breakthrough in increasing the productivity of chromatographic separations; however, a significative decrease in productivity can still be observed as the level of purification increases. For this reason, some authors have been pursuing the use of hybrid processes, combining SMB chromatography and crystallization in order to obtain an increase in productivity (Lim et al, 1995;Lorenz et al, 2001;Bléhaut et al, 2001;Gedicke, 2005;Lorenz et al, 2006). The general concept of the hybrid process is based on using chromatography as a prepurification stage, followed by a crystallization step to achieve the final purification.…”
Section: Enantioseparation Via Chromatography and Crystallizationmentioning
confidence: 99%
“…The SMB technology was a breakthrough in increasing the productivity of chromatographic separations; however, a significative decrease in productivity can still be observed as the level of purification increases. For this reason, some authors have been pursuing the use of hybrid processes, combining SMB chromatography and crystallization in order to obtain an increase in productivity (Lim et al, 1995;Lorenz et al, 2001;Bléhaut et al, 2001;Gedicke, 2005;Lorenz et al, 2006). The general concept of the hybrid process is based on using chromatography as a prepurification stage, followed by a crystallization step to achieve the final purification.…”
Section: Enantioseparation Via Chromatography and Crystallizationmentioning
confidence: 99%
“…Such enrichment works because it moves the system composition from a region of a phase diagram where thermodynamics drives production of crystals of a racemate compound to a region where pure enantiomer can be crystallized. This has been done using a chromatographic technique to adjust the solution composition and allow preferential crystallization of a pure enantiomer (46). Encarnación suggested that the enrichment could be done by converting one enantiomer into the other with a reaction enhanced by an enzyme in a reactive crystallization process.…”
Section: Chiral Separations Chemical Reactions and Crystallizationmentioning
confidence: 99%
“…The experimental procedure for mandelic acid has been chosen according to Lorenz et al 23 The solution used for the crystallization experiment was prepared according to the solubility data of RS-mandelic acid at 408C. 25 Initial masses of substance and water and experimental conditions were summarized in Table 2.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%
“…After generating an enantiomeric excess for example by a partially selective synthesis or by a chromatographic and a following evaporation step, the state A in Figure 2b located within the three-phase region can be reached. 22,23 As it is also depicted in Figure 2b seeding with crystals of the enantiomer E 1 initializes the crystallization of merely this enantiomer and the mother liquor composition tends towards point Z. Up to a certain time pure E 1 can be gained until the spontaneous nucleation of the racemic compound (rac) will occur and the trajectory will be attracted to the eutectic point E. The same considerations are valid for the crystallization of E 2 in the right-hand side three-phase region after seeding the enantiomerically enriched solution with E 2 .…”
mentioning
confidence: 98%
See 1 more Smart Citation